Foreign and domestic collaboration, product innovation novelty, and firm growth - Hsieh, Wan-Lin; Ganotakis, Panagiotis; Kafouros, Mario; Wang, Chengqi (Wiley, 2018)
Although prior research underscores the benefits of external collaboration for a firm's innovative output, little research has examined the role that collaboration plays across the different stages of the innovation process. Drawing from organizational learning theory, this article examines (1) how collaboration with domestic partners assists in the formation of collaborations with foreign partners, (2) how knowledge from these collaborations is associated with product innovation at different levels of novelty, and (3) how the relationship between the level of innovation novelty and firm growth is influenced by whether the focal firm engages in open or closed innovation and the origin of the collaborator (foreign or domestic). Three key findings emerge from the econometric analysis of a sample of 1684 Taiwanese firms. First, domestic collaborations assist in the formation of foreign collaborations when the partner type is the same. Second, the level of innovation novelty is associated with the type and geographic location of partners. This study differentiates among noninnovating firms, incremental innovators, and radical innovators and demonstrates that the role of partners changes as the number of countries in which a firm collaborates with each partner type increases. Third, only radical innovation is relevant to firm growth, regardless of whether it is developed internally or through collaboration with domestic or foreign partners.